Volunteers’ well-being with the maqashid shariah approach: Evidence from charitable organizations in Indonesia - Dzuliyati Kadji; Dwi Retno Widiyanti (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This study aims to analyze the influence of the five dimensions of Maqashid Sharia on the life satisfaction of Muslim volunteers of charitable organizations di Indonesia.Methodology – This study used data from the World Value Survey Wave 7 with a sample of 504 muslim volunteers who are active members of charitable organizations in Indonesia. The data were analyzed using logit and probit regression.Findings – The results of this study reveal that both the logit and probit methods consistently show that from the five Maqashid Syariah dimensions, the dimensions of faith, life and wealth positively influence the life satisfaction of volunteers. In contrast, the intellectual and descendants dimensions are not significant to the life satisfaction of volunteers. Furthermore, the wealth dimension has the greatest tendency toward the life satisfaction of Muslim volunteers from charitable organizations in Indonesia. Implications – This research has implications for developing empirical analysis of individual well-being in Indonesia and the research on the subjective well-being of volunteers, which is part of a national and international analysis of economic happiness linked with the Islamic economy, specifically maqashid sharia as an essential part of Muslim individuals. Originality – This research is expected to fill in the existing research gap regarding welfare analysis of volunteer life satisfaction from an Islamic economic point of view through the Dimension of Maqashid Sharia. This study employs volunteers as objects because Indonesian volunteers are the most numerous in the world, contributing to Indonesia's position as the most generous country in the world.